Spray drying of fenofibrate loaded nanostructured lipid carriers - Dengning Xia; Neha Shrestha; Jacco van de Streek; Huiling Mu; Mingshi Yang (Elsevier, 2016)
The conversion of aqueous dispersion of nanostructured lipid carriers (NLCs) into dry powder by spray drying could be a useful approach to render NLCs with better physical chemical stability than the aqueous dispersion. In this study, aqueous NLC dispersion containing fenofibrate was converted into dry, easily reconstitutable powder using spray drying. A central composite face centered design (CCFD) was used to investigate the influence of the ratio of lipid to protectant (mannitol and trehalose) and crystallinity of spray-dried powder on the particle size, yield and residual moisture content of the dried powder. A linear relationship (R2 = 0.9915) was established between the crystalline content of the spray-dried powders against the ratio of mannitol to trehalose from 3:7 to 10:0 (w/w). Spray drying of NLC aqueous dispersion using a mannitol and trehalose mixture resulted in an increase in particle size of the NLCs after reconstitution in water as compared to that in the initial aqueous dispersion. The decrease in crystallinity of the dry powder by reducing the ratio of mannitol to trehalose could improve the reconstitution of the NLCs in water. However the yield and residual moisture content of dry powder decreased with an increase in the ratio of mannitol to trehalose. Lipid nanoparticles were able to retain the drug incorporation and the prolonged drug release profile after spray drying. The experimental model was robust, and suggested that spray drying is a viable technique for the conversion of NLCs into dry powder.